Real-life implementation of a G6PD deficiency screening qualitative test into routine vivax malaria diagnostic units in the Brazilian Amazon (SAFEPRIM study). - Jose Diego Brito-Sousa; Felipe Murta; Sheila Vitor-Silva; Vanderson S Sampaio; Maxwell O Mendes; Marcelo A M Brito; Talita S B Batista; Alicia P C Santos; Leonardo L G Marques; Laila R A Barbosa; Marly M Melo; Djane C Baia-; et al. (Public Library of Science (PLoS), 2021)
Background Glucose-6-phosphate dehydrogenase (G6PD) deficiency greatly hinders Plasmodium vivax malaria radical cure and further elimination due to 8-aminoquinolines-associated hemolysis. Although the deleterious health effects of primaquine in G6PD deficient individuals have been known for over 50 years, G6PD testing is not routinely performed before primaquine treatment in most P. vivax endemic areas. Method/principal findings The qualitative CareStart G6PD screening test was implemented in 12 malaria treatment units (MTUs) in the municipality of Rio Preto da Eva, Western Brazilian Amazon, a malaria endemic area, between February 2019 and early January 2020. Training materials were developed and validated; evaluations were conducted on the effectiveness of training health care professionals (HCPs) to perform the test, the interpretation and reliability of routine testing performed by HCPs, and perceptions of HCPs and patients. Most HCPs were unaware of G6PD deficiency and primaquine-related adverse effects. Most of 110 HCPs trained (86/110, 78%) were able to correctly perform the G6PD test after a single 4-hour training session. The test performed by HCPs during implementation showed 100.0% (4/4) sensitivity and 68.1% (62/91) specificity in identifying G6PD deficient patients as compared to a point-of-care quantitative test (Standard G6PD). Conclusions/significance G6PD screening using the qualitative CareStart G6PD test performed by HCPs in MTUs of an endemic area showed high sensitivity and concerning low specificity. The amount of false G6PD deficiency detected led to substantial loss of opportunities for radical cure.